Training and stability of the intrinsic two-way shape memory effect in Ni-Ti alloys - Scherngell, H.; Kneissl, A.C. (Scripta materialia, 1998)
The degradation of the discussed intrinsic TWSME can be divided into two stages. In the initial stage of thermal cycling a rather strong decay can be observed which is ascribed to the rearrangement of dislocations. In the latter stage the degradation is more gradual and the controlling mechanism is thought to be the introduction of additional dislocations. Especially the degradation in the latter stage seems to be possible to control. By applying an appropriate thermal treatment a stability of the effect, suitable for technical application, can be achieved after cycling in the element.